The border spaces of the European Community in audiovisual fiction: The case of Iberian television series - Reyes-Corredera, Sergio Jesús; Silva, Paulo; Gámir Orueta, Agustín (Editorial CSIC, 2025)
Greater collaboration between the Spanish and Portuguese audiovisual industries in the form of co-productions for television channels has been seen in recent years. This is evidence of a shared audience and the public's interest in this type of content. This paper seeks to analyse the representations of the territories filmed in these co-productions. This analysis is based on an exhaustive review of eleven television series and 1,762 clips shot on location. The geographical methodological approach provides a more complete vision of Iberian co-productions, as well as the depiction of the geographical areas in question. This methodology can be applied to other geographical contexts and contribute to the understanding of cross-border dynamics in the audiovisual field. The primary findings demonstrate that these co-productions effectively expand their audience, showcasing the tangible impact of European policies that promote and facilitate cross-border collaboration. Furthermore, an in-depth analysis of the clips has revealed that the majority of the co-productions reflect a combination of contemporary narratives with historical urban contexts, thus enabling the city patterns to be defined according to their characteristics. Finally, the geographical distribution of the scenes shows that border regions are still underrepresented, with the exception of the Galicia-North Portugal corridor, one of the largest conurbations on the Iberian Peninsula. We therefore advocate for greater inclusion of depopulated and rural areas to foster a more comprehensive cultural and geographical narrative.
Keywords: Coproducción audiovisual - Europa; Industria audiovisual - Península Ibérica; Audiovisual co-productions; Spain and Portugal border; Television series; Cross-border cultural collaboration; Geographical Imaginary; European Community policy